Peatlands Restoration As A Potential Solution To Resolve Peatlands Damage Based On Sustainable Development Goals (SDGS) In Sungai Tohor, Indonesia - Handoko, Tito; Tiyas Tinov; Achmad Fajri Febrian; Risky Arya Putri; Frini Karina Andini; Ogi Rifansyah (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
Peatland restoration is a potential solution to resolve peatland damage but faces an economic-social-environmental exchange (Sustainable Development Goals) that results in strong disagreements between stakeholders who have different interests such as company, community and local or regional government concessions. Successful peatland restoration will depend on how various priorities have been reconciled, as much as it depends on improving governance and cross-sector collaboration well done. The purpose of this paper is to find a solution how to be managing peatlands in Sungaitohor, Indonesia. We use social maps to show the communities concern to restoration of degraded peatland, we try to compare the level of public awareness to prevention efforts and the restoration of peatland damaged by fires Forest and peatlands. The findings of this paper are social map, that explain the community’s participation to efforts of peatland restoration in Sungai tohor, Indonesia.